High CT Attenuation Values Relative to the Brainstem Predict Fungal Hyphae Within the Sinus - Kikuta, Shu; Han, Bing; Yoshihara, Shintaro; Nishijima, Hironobu; Kondo, Kenji; Yamasoba, Tatsuya (Frontiers in Surgery, 2022)
Objectives There is currently no established objective diagnostic indicator for the differentiation of sinus fungal ball (SFB) from unilateral nonfungal chronic sinusitis (UCRS). This study evaluated whether computed tomography (CT) attenuation values relative to those of the brainstem (relative CT number) are useful for differentiating SFB from UCRS. Materials and Methods Consecutive patients who were pathologically diagnosed with SFB or UCRS between 2013 and 2021 were retrospectively identified. The relative CT numbers of region of interest (ROIs) within the sinuses were compared between the two patient groups. Factors with predictive power for differentiating SFBs from UCRSs were identified by uni/multivariable logistic regression analyses. Results One hundred and eighty-three patients with unilateral chronic sinusitis were finally analyzed (SFB, 86 cases; UCRS, 97 cases). Regardless of the presence or absence of calcified lesions, the relative CT numbers in SFB were significantly higher than those in UCRS. ROIs showing high relative CT numbers were those where fungal hyphae were present. In the uni/multivariable logistic regression analysis, age (p < 0.001), relative CT number (p < 0.001), and calcification (p = 0.002) had predictive value for distinguishing SFB from UCRS. Within those cases not showing calcification, age (p = 0.004) and relative CT number (p < 0.001) were predictive factors for differentiating SFB from UCRS. A relative CT number >1.5 was significantly associated with SFB (sensitivity, 70%; specificity, 91%), with a significantly larger area under the receiver operating characteristics curve than age. Conclusions High relative CT numbers within the sinus are strongly associated with the presence of fungal hyphae, and measurement of relative CT number is a powerful adjunctive diagnostic method for distinguishing between SFB and UCRS.